The impact of education, training and work experience on job satisfaction and job performance - Muntazeri, Satrio; Indrayanto, Adi (Jurnal Akuntansi, Manajemen dan Ekonomi, 2018)
The purpose of this research is to confirm and integrate the Duggan & Horton (2004) and Robbins (2005) founding on the effect of career development on job satisfaction, and the impact of job satisfaction on employee performance. Existing literatures and researches are only talking about the influence of both career development and job satisfaction as independent variables on employee performance. The sample of this research was 80 employees from Bank Rakyat Indonesia (BRI) in Purbalingga. Those samples are determined using the Slovin method. Data were calculated and analyzed using the IBM Statistical Package for Social Science (SPSS) version 25. The results of this research indicate that (1) Education has a positive and significant influence on job satisfaction. (2) Training has a positive and significant influence on job satisfaction. (3) Work experience has a positive and significant influence on job satisfaction. (4) Job satisfaction has a positive and significant influence on employee performance.